Geburtenwende in Deutschland – was ist dran und was sind die Ursachen? - Martin Klein; Tobias Weirowski; Rahel Künkele (Wirtschaftsdienst, 2016)
Deutschland weist im europäischen Vergleich seit langem besonders geringe Geburtenraten und einen hohen Altersdurchschnitt der Bevölkerung auf. Nun zeichnet sich aber eine Wende in der Geburtenentwicklung ab, die von den Großstädten ausgeht und sich von dort sukzessive ausbreitet. Der zeitliche Schwerpunkt dieser Geburtenwende liegt in den Jahren 2009 bis 2011, zeitgleich mit der Wirtschafts- und Finanzkrise dieser Jahre und in unmittelbarer Folge zu der 2007/2008 vollzogenen familienpolitischen Wende. – – In comparison to other European countries, Germany is among those with the lowest birth rate and the highest median age of the population. Yet recently there are signs of a trend change in German fertility. For a decade now, birth rates in larger German cities have been on the rise, and this new baby boom has spread to smaller urban regions, leading to a trend change in overall fertility. The main years of this trend change are 2009 through 2011, parallel to the economic and fi nancial crises of that time and following in the wake of important changes in German family policy in 2007/2008.
Keywords: J10; J11; J13; 330